Incidence Of Photokeratitis In Factory Workers After Ultraviolet C Exposure and Its Management : A Case Series: Poster Presentation - Case Series - Ophthalmologist - dr. ANDREAS SURYA ANUGRAH, Sp.M; dr. Rima Melati, M.KK, SpAk(K), Sp.Ok(K) (Majalah Oftalmologi Indonesia, 2023)
Introduction : Ultraviolet C lamps have been used in industry and healthcare to disinfect rooms, air, water, and surfaces. However, exposure to UV-C may cause serious damage to human eyes. Case Illustration : This were photokeratitis case series of 4 factory workers that occurred simultaneously after 4 hours exposure to UV-C lamp about one meter away without any protective eyewear. Several hours after exposure, they complained swollen, red and watery eyes, photophobia, sandy sensation, and blurry vision. One day after, they were taken to the Emergency Unit. Diagnosis of photokeratitis was established by using biomicroscopic examination. All subjects were treated with antibiotic eye drops, lubricants, oral anti-inflammatory drugs, and cold compress. Evaluation after 1 week showed clinical improvement and all subjects were able to return to work normally. Discussion : Photokeratitis or ultraviolet keratitis is an inflammatory condition of the cornea after ultraviolet exposure for 30 minutes to 12 hours. The corneal epithelial layer functions as protector for corneal stroma and endothelium. However, the longer corneal epithelium is exposed to ultraviolet light, the more damaged it is. This caused subepithelial nerve plexus exposed, resulting in severe pain, photophobia, and bilateral epiphora. Injection and chemosis of bulbar conjunctiva, epiphora, and punctate keratopathy of cornea were found in examination. The management given is supportive therapy, and should be immediately given until corneal epithelium healed. Conclusion : Photokeratitis may occurred in daily work. Regulation, warning, training and appropriate protective eyewear for workers in workplaces using UV-C lamps are mandatory. Immediate and adequate treatment can save the sight of workers exposed to UV-C.